2012
DOI: 10.1007/s11682-012-9210-3
|View full text |Cite
|
Sign up to set email alerts
|

Volunteerism and self-selection bias in human positron emission tomography neuroimaging research

Abstract: Scientists have known for decades that persons who volunteer for behavioral research may be different from those who decline participation and that characteristics differentiating volunteers from non-volunteers may vary depending on the nature of the research. There is evidence that volunteer self-selection can impact representativeness of samples in studies involving physically or psychologically stressful procedures, such as electric shocks, sensory isolation, or drug effects. However, the degree to which se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…They also had higher cognitive test scores, fewer IADL impairments, and, over 6–8 years of follow-up, had significantly lower mortality rates than the randomly selected participants (Ganguli 1998). Using a different conceptual paradigm to study volunteerism and self-selection bias, a recent study (Oswald 2013) recruited by advertisement a sample of healthy young adults aged, assessed their demographic and personality characteristics, and offered them the opportunity to enroll in a positron emission tomography (PET) study involving intravenous amphetamine administration. Those who consented to this PET study were more likely to be male and to score significantly higher on sensation-seeking traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also had higher cognitive test scores, fewer IADL impairments, and, over 6–8 years of follow-up, had significantly lower mortality rates than the randomly selected participants (Ganguli 1998). Using a different conceptual paradigm to study volunteerism and self-selection bias, a recent study (Oswald 2013) recruited by advertisement a sample of healthy young adults aged, assessed their demographic and personality characteristics, and offered them the opportunity to enroll in a positron emission tomography (PET) study involving intravenous amphetamine administration. Those who consented to this PET study were more likely to be male and to score significantly higher on sensation-seeking traits.…”
Section: Discussionmentioning
confidence: 99%
“…Since the characteristics of those who do not participate in a given study are typically unknown, the nature and extent of “volunteer bias” and “selection bias” are difficult to determine. Previous studies have shown that volunteers are younger, better educated, healthier, cognitively better than those randomly selected for research (Ganguli 1998; Jaramillo 2007); another study investigated personality traits of those who agreed to participate in a functional imaging study (Oswald 2013). How these factors actually influence the imaging study results is usually a matter for speculation.…”
Section: Introductionmentioning
confidence: 99%
“…They found that volunteers for the prison study had higher scores on aggression, authoritarianism, narcissism, and social dominance but lower scores on empathy and altruism. Recently, Oswald, Wand, Zhu, and Selby (2013) found that volunteers for a neuroimaging study had higher scores on sensation seeking compared to nonvolunteers. Collectively, there is convincing evidence to suggest that volunteers for research studies have certain experiences and characteristics that could threaten the generalizability of empirical studies.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…However, our fMRI participants consisted of a more variable sample who volunteered for fMRI scanning at different months of the year in response to ads placed around campus. A recent study showed that PET scan volunteers significantly scored higher in sensation-seeking trait compared to behavior-only volunteers (Oswald et al, 2013).…”
Section: Discussionmentioning
confidence: 99%